Multiple interest accommodation in African forest management projects: between pragmatism and theoretical coherence - Antona, M.; Babin, D. (2001)
In the past in Africa, State forest administration took nominal control of local forest management from rural populations. This control, based on a European concept of management, gradually deteriorated and the methods of classical forest management are no longer suited to existing conditions. This has led to a need for processes to accommodate multiple interests. Funding agencies, firms, NGOs and governments have tried different participatory approaches in their forest projects. In this evolution, social sciences have been absent or overshadowed by other disciplines. Too often, the coherence of social science has been replaced with anecdotal pragmatism. We therefore investigated the contributions of collective action theories. From this analysis, we propose a framework for analysing accommodation in forest management projects at different stages (objective setting, context identification, appraisal, implementation and evaluation). We applied the Multiple Interest Accommodation Assessment (MIAA) framework to forestry projects and environmental policies in nine African countries. Using this framework to compare these experiences, we identified key issues for the MIA processes in complex forest management situations.